REPRESENTASI PSIKOLOGI PEREMPUAN SUNDA DALAM FILM BEFORE NOW AND THEN (NANA) KARYA KAMILA ANDINI: PSYCHOLOGICAL REPRESENTATION OF SUNDAN WOMEN IN THE FILM BEFORE NOW AND THEN (NANA) BY KAMILA ANDINI - Alfina Pebriani; Ratnawati (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2024)
In Sundanese society, female characters have a very important role. This role can be judged from the appearance of the female characters featured in literary works and films. One of them is the film Before Now and Then (Nana) by Kamila Andini. No one has ever studied it, especially in the psychological aspect of literature. This film also uses a lot of self-defense systems in his personality. The aim of this research is to describe the structure of the film Before Now and Then (Nana) by Kamila Andini and to describe the representation of Sundanese women in the film Before Now and Then (Nana) by Kamila Andini. This research method uses descriptive analysis, data collection techniques, namely non-participant observation and literature review. The instrument used is a data card and the output of this research is a scientific article published in a national journal. The results of research regarding film structure have themes of struggle and Sundanese women; The flow used is the forward flow; There are 34 characters in this film; there are 38 backgrounds; the film title Before Now and Then (Nana) refers to the main character, namely Nana; the point of view used is first person; there are 4 language styles and 72 tones; 68 symbolism; and this film includes situational irony. There are 12 ID personality analyzes in the film, 50 ego personality analyzes and 13 superego personality analyses. Keywords: film structure, representation, Sundanese women